How User Satisfaction Impacts The Effectiveness of The Indonesia Integrated Electronic Business Licensing Management Information System as Sustainable Design for Enviromental Business? - Putri Maulida Sarie; Alfian Alfian (Management Analysis Journal, 2023)
This study aimed to investigate the impact of user satisfaction on the effectiveness of the Indonesia Integrated Electronic Business Licensing Management Information System. The research population comprised members of Business Actors and Licensing Associations in Indonesia, with a sample size of 44 members selected using a simple random sampling technique. Multiple linear regression analysis using SPSS version 26 was used for data analysis. The findings indicate that the effectiveness of the integrated licensing management information system is influenced by user satisfaction. The results indicate that the system is highly effective in terms of user satisfaction. This research can be utilized as an evaluation tool for improving and developing the Electronically Integrated Business Licensing Management Information System in Indonesia.